Nurses’ Role Ambiguity: A Scoping Review - Sekar Putri Kirana; Yuliani Setyaningsih; Chriswardani Suryawati (Green Publisher Indonesia, 2026)
Background: Nurses are frontline healthcare professionals in hospital settings, operating within complex clinical environments, high job demands, and rapidly evolving healthcare systems. These conditions contribute to role ambiguity, a multidimensional phenomenon characterized by unclear responsibilities, expectations, and professional boundaries, which may affect nurses’ performance, psychological well-being, and care quality. Aim: This scoping review aimed to clarify the concept of role ambiguity, synthesize current evidence regarding its occurrence among hospital nurses, and identify multilevel factors influencing its development. Methods: A scoping review methodology was employed. Literature searches were conducted in Google Scholar, ProQuest, ScienceDirect, and Wiley using the keywords “nurse” OR “nurses” AND “role ambiguity” AND “hospital”. Based on predefined inclusion criteria, ten original research articles published between 2020 and 2026 were selected and analyzed. Results: Role ambiguity is influenced by individual, organizational, and systemic factors. Emotional intelligence plays a critical role in regulating responses to ambiguous situations, while social support from supervisors and colleagues, along with organizational clarity regarding responsibilities and professional boundaries, reduces role ambiguity. Additionally, digitalization, adaptation to evolving work systems, and structured education and simulation programs contribute to improving role clarity. Conclusion: Role ambiguity among hospital nurses is a complex, multidimensional issue requiring multilevel organizational and professional strategies. Future longitudinal and methodologically rigorous research is needed to support sustainable workforce and healthcare system improvement.